2016
DOI: 10.1016/j.bbi.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant imipramine diminishes stress-induced inflammation in the periphery and central nervous system and related anxiety- and depressive- like behaviors

Abstract: In order to relieve anxiety and depression accompanying stress, physicians resort to tricyclic antidepressants, such as imipramine. We had previously shown that imipramine reversed stress-induced social avoidance behavior, and down-regulated microglial activation 24 days after stress cessation. To further characterize the effects of imipramine on stress induced neuroimmune dysregulation and associated changes in behavior, the aims of this study were to determine if imipramine 1) ameliorated stress-induced infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 63 publications
1
53
0
2
Order By: Relevance
“…However, previous studies reported chronic stress increased the plasma level of IL-6and TNF-α 24, 25 , while another report showed that restraint stress caused a significant decrease in the concentrations of circulating IFN-γ, IL-12(p40), IL-12(p70), IL-4, and IL-5 26 . Recently, Smith et al .…”
Section: Discussionmentioning
confidence: 88%
“…However, previous studies reported chronic stress increased the plasma level of IL-6and TNF-α 24, 25 , while another report showed that restraint stress caused a significant decrease in the concentrations of circulating IFN-γ, IL-12(p40), IL-12(p70), IL-4, and IL-5 26 . Recently, Smith et al .…”
Section: Discussionmentioning
confidence: 88%
“…Chronic inflammation is a key factor in depressive and obesity states (Miller and Raison, 2015; Ramirez and Sheridan, 2016). Changes in central Lipocalin-2 ( Lcn2 ) are associated with depression and anxiety (Mucha et al, 2011; Ferreira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the classical tricyclic antidepressant imipramine prevents neuroinflammation and behavioral deficits (depression- and anxiety-like behaviors) caused by CSDS [17, 18]. In addition, studies without stress exposure found that interferon-alpha (IFN-α) therapy elicited neuroinflammation as well as depression-like behaviors [19], both of which were prevented by minocycline, an inhibitor of microglial activation [20].…”
Section: Introductionmentioning
confidence: 99%